2022
DOI: 10.1021/acs.est.2c02974
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Adsorption of Gaseous Hg0 and Hg(II) by Regenerable Monolithic FeMoSx/TiO2: Mechanism and its Application in the Centralized Control of Hg Pollution in Coal-Fired Flue Gas

Abstract: FeMoS x /TiO2 was investigated as a regenerable sorbent to simultaneously adsorb Hg0 and Hg­(II) from coal-fired flue gas for the centralized control of Hg pollution discharged from coal-fired power plants. The performance of FeMoS x /TiO2 for Hg­(II) and/or Hg0 adsorption was evaluated on a fixed-bed reactor at 80 oC, and the mutual interference between Hg0 adsorption and Hg­(II) adsorption was analyzed using individual adsorption, simultaneous adsorption, and two-stage adsorption. FeMoS x /TiO2 displayed an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 50 publications
(105 reference statements)
0
16
0
Order By: Relevance
“…The kinetics of HgCl 2 adsorption onto sulfureted HPMo/γ-Fe 2 O 3 is deduced in the SI, and it was demonstrated that HgCl 2 was mainly adsorbed on the S 0 adsorption sites. Therefore, the kinetics for HgCl 2 adsorption was approximately described as prefix− normald [ Hg ( g ) 2 + ] normald t = k 2 θ 3 [ S 2 ] [ φ 1 ] exp ( k 2 false[ normalS 2 false] θ 3 t ) = A 2 0.25em exp ( B 2 t ) A 2 = k 2 θ 3 [ S 2 ] [ φ 1 ] B 2 = k 2 [ ...…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The kinetics of HgCl 2 adsorption onto sulfureted HPMo/γ-Fe 2 O 3 is deduced in the SI, and it was demonstrated that HgCl 2 was mainly adsorbed on the S 0 adsorption sites. Therefore, the kinetics for HgCl 2 adsorption was approximately described as prefix− normald [ Hg ( g ) 2 + ] normald t = k 2 θ 3 [ S 2 ] [ φ 1 ] exp ( k 2 false[ normalS 2 false] θ 3 t ) = A 2 0.25em exp ( B 2 t ) A 2 = k 2 θ 3 [ S 2 ] [ φ 1 ] B 2 = k 2 [ ...…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that S 2 2– in FeS 2 /MoS 3 may act as an oxidant for Hg 0 oxidation . Therefore, the chemical adsorption of Hg 0 onto sulfureted HPMo/γ-Fe 2 O 3 was approximately expressed as follows ,, Hg false( normalg false) 0 Hg false( ad false) 0 Hg false( ad false) 0 + normalS 2 2 normalS 2 + HgS …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations